Basic Conceptual Structure of Evolutionary Ecology - Parentoni Martins, Rogério (European Journal of Ecology, 2021)
Concepts are linguistic structures with specific syntax and semantics used as sources of communicating ideas. Concepts can be simple (e.g., tree), complex (e.g., adaptation) and be part of a network of interactions that characterize an area of scientific research. The conceptual interrelationships and some evolutionary consequences upon which these interrelations are based will be addressed here. The evolutionary ecology is an area of research from the population evolutionary biology that deals mainly with the effect of positive natural selection on panmictic and structured populations. Environmental factors, conditions and variable resources in time and space, constitute the selective agents that act on the phenotypic and genotypic variation of populations in a single generation, could result in evolutionary adaptations, which are simply those traits that are most likely to confer survival and reproduction (evolutionary fitness) of the phenotypes that carry them in successive generations. The bases of adaptation are mainly genetic and transmitted vertically (classical Mendelian mechanisms) or horizontally (in the case of microorganisms). The phenotypic variance of the population is a conjoint consequence of the additive genotypic variance (heritability), nonadditive variance (dominance and epistasis), pleiotropy and the interaction between genotype and environment. The ability of the same genotype to respond to spatial environmental variations can result in phenotypic plasticity that manifests itself through reaction norms. The total phenotypic variation and its genetic and environmental components influence the ability of a population to evolve (evolvability).